(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Today, the need for mathematics is increasing. In the educational process, innovative pedagogical technologies and quality of education are considered as the most effective tools. In order to improve the quality of education, this article discusses the effective use of pedagogical and information technologies in solving problems related to vector theory and geometry, what to pay attention to, and how to apply them in practice.